The Challenge of Copyright in the Digital Age (2006)
The author explains how the revolution in the way new technology can reproduce, disseminate, and store digital information, including copyrighted works, is truly a double-edged sword for authors and right-holders. The challenge of copyright in the digital age is to preserve the author’s and right-holder’s incentive to create new works and use new technologies to distribute them to users and consumers in the face of a huge competitive threat from the illicit use of technology by infringers. Finally, the author warns about the debate that new technologies often prompt about whether the set of exclusive rights granted to authors and right-holders should be modified, either with new or broadened rights or new or broadened exemptions, to continue to serve the purpose of copyright.